The little giant book of tongue twisters - Artell, Mike; Rosenbloom, Joseph; Kendrick, Dennis (New Delhi Goodwill Pub. House, 2008)
An illustrated collection of hundreds of difficult tongue twisters, arranged alphabetically.
"Published by arrangement with Sterling Publishing Co., Inc., New York"--T.p. verso.
Keywords: Tongue twisters